CBIO-11. HISTONE H3.3 G34R/V MUTATIONS STIMULATE PEDIATRIC HIGH-GRADE GLIOMA FORMATION THROUGH THE INDUCTION OF CHROMOSOMAL INSTABILITY. (12th November 2021) - Day, Charles; Grigore, Florina; Langfald, Alyssa; Hinchcliffe, Edward; Robinson, James
Abstract: H3.3 G34R/V mutations are drivers of high-grade pediatric glioma (pHGG). H3.3 G34R/V mutations are linked to altered H3.3 K36 trimethylation (H3K36me3); implicating epigenetic gene regulation as a possible contributor to pHGG formation. Here we show that H3.3 G34R/V also induces chromosomal instability (CIN); a hallmark of pHGG. If CIN promotes pHGG formation is unknown. We observed that H3.3 G34 mutant pHGG cells have reduced mitotic H3.3 S31 phosphorylation compare to WT H3.3 cell lines. And, H3.3 G34R reduced Chk1 phosphorylation at S31 by >90% in an in vitro kinase assay. Chk1 regulates chromosome segregation through phosphorylation of pericentromeric H3.3 S31 during early mitosis. Overexpression of H3.3 G34R or non-phosphorylatable S31A in H3.3 WT, diploid cells caused a significant increase in CIN. Likewise, H3.3 G34 mutant pHGG cells have significantly elevated rates of CIN as compare to H3.3 WT pHGG cells. During normal cell division, phospho-S31 is lost in anaphase. However, following chromosome missegregation, phospho-S31 spreads and stimulates p53-induced cell cycle arrest. Here we show that WT p53 cells expressing mutant G34 fail to arrest following chromosome mis-segregation. These studies demonstrate that H3.3 G34R/V mutations are sufficient to transform normal, diploid cells into proliferating CIN cells. To determine if this process contributes to tumorigenesis, we used RCAS Nestin-TVA mice to overexpress H3.3 WT, G34R, or S31A – P2A-linked to PDGFB expression in glial precursor cells of newborn mice. Over 100 days, S31A and G34R mice had drastically reduced survival (averaging 77, 81, and 100 days for S31A, G34R, and WT). Furthermore, most G34R and S31A mice developed HGG, while H3.3 WT mice remained tumor-free. Our work implicates CIN as a driver of H3.3 G34 mutant pHGG formation. Our ongoing studies utilize K36M and double mutants to further define the contributions of S31 phosphorylation (CIN) and H3K36me3 (epigenetic gene regulation) to tumorigenesis.